GERAKAN LITERASI ASMAUL HUSNA BERBASIS PERMAINAN SCRUMBLE CARD PADA MADRASAH IBTIDAIYAH AL-ISLAMIYAH - Mardianto Mardianto; Nirwana Anas; Raden Fadli Daulay; Barani Saragih; Three Wulan Ramadhani (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2022)
Indonesia is ranked tenth from the bottom which is a low country in terms of literacy activities. Therefore, new innovations in literacy activities are needed, especially those that can be done simply but have a big impact. Literacy activities are activities carried out in the field of education, precisely in schools. The school literacy movement (GLS) refers to learning materials, such as moral aqidah subjects which discuss Asmaul Husna or the 99 names of Allah SWT. Many literacy activities regarding Asmaul Husna have been carried out but have had a less than optimal impact. Therefore, a new innovation is needed, such as combining the literacy movement with a game-based learning model. The results of this innovation will be known if it is not tested directly. Therefore, the researcher wanted to analyze how the Asmaul Husna literacy movement was combined with the scramble card game. The research method used is a descriptive method with a qualitative approach. The results obtained after the research revealed that the innovation of combining Asmaul Husna with the Sccrumble Card game increased the enthusiasm of students to understand and indirectly combined it with their game of memorizing the 99 names of Asmaul Husna.